Case Report: The Cox-Maze IV Procedure in the Mirror: The Use of Three-Dimensional Printing for Pre-operative Planning in a Patient With Situs Inversus Dextrocardia - Song, Long; Fan, Chengming; Zhang, Hao; Liu, Hongduan; Iroegbu, Chukwuemeka Daniel; Luo, Cheng; Liu, Liming (Frontiers in Cardiovascular Medicine, 2021)
The safety and efficacy of the Cox-Maze IV procedure (CMP-IV) for situs inversus dextrocardia patients with atrial fibrillation is yet to be determined. Herein, we present the case of a 39-year-old male patient admitted to our cardiac center following progressive exertional dyspnea. The patient was diagnosed with situs inversus dextrocardia, severe mitral regurgitation, and paroxysmal atrial fibrillation. A three-dimensional (3D) heart model printing device embedded with designated ablation lines was used for preoperative planning. Mitral valvuloplasty, CMP-IV, and tricuspid annuloplasty were performed. The patient had an uneventful recovery and was in sinus rhythm during a 12-month follow-up period using a 24-hour Holter monitoring device. The case herein is one of the first to report on adopting the CMP-IV procedure for situs inversus dextrocardia patients with complex valvuloplasty operation. In addition, the 3D printing technique enabled us to practice the Cox-maze IV procedure, given the patient's unique cardiac anatomy.